Synthesis and Characteristics of Double-Shell Mesoporous Hollow Silica Nanomaterials to Improve CO2 Adsorption Performance - Jong-tak Lee (MDPI AG, 2021)
To improve the adsorption performance of carbon dioxide, which is considered the main culprit of greenhouse gases, the specific surface area and high pore volume of the adsorbing material should be considered. For a porous material, the performance of carbon dioxide adsorption is determined by the amine groups supporting capacity; the larger the pore volume, the greater the capacity to support the amine groups. In this study, a double-shell mesoporous hollow silica nanomaterial with excellent pore volume and therefore increased amine support capacity was synthesized. A core–shell structure capable of having a hollow shape was synthesized using polystyrene as a core material, and a double-shell mesoporous shape was synthesized by sequentially using two types of surfactants. The synthesized material was subjected to a sintering process of 600 degrees, and the N2 sorption analysis confirmed a specific surface area of 690 m2/g and a pore volume of 1.012 cm3/g. Thereafter, the amine compound was impregnated into the silica nanomaterial, and then, a carbon dioxide adsorption experiment was conducted, which confirmed that compared to the mesoporous hollow silica nanomaterial synthesized as a single shell, the adsorption performance was improved by about 1.36 times.